Characteristics of Elderly Home Care Volunteers in Western of Thailand - Whangmahaporn, Piyakorn (Asian Crime and Society Review, 2020)
Research characteristics of elderly home care volunteers in Western of Thailand have several objectives 1) to study the factors affecting the characteristics of elderly home care volunteers 2) to compare the differences in characteristics of elderly home care volunteers by personal factors and 3) to study the problems and obstacles while serve as an elderly home care volunteer. This research was mixed methods research. Key informants in the qualitative research were 20 elderly home care volunteers. Population in the quantitative research was elderly home care volunteers 17,760 people, area scope was province of Western Thailand which were Ratchaburi, Kanchanaburi, Tak, Prachuap Khiri Khan and Phetchaburi. The instrument used to collect data was semi-structured interview and questionnaire. Statistics used in data analysis were frequency, percentage, One -way MANOVA and Multiple Linear Regression Analysis. The results of this study revealed that most volunteers had a hard working and satisfied with their work. Elderly home care volunteers with different in gender, age, religion and occupation had the same characteristics, except the level of education, marital status and period of time work as the volunteers. All factors affecting the characteristics of elderly home care volunteers. Problems and obstacles that occurred when being an elderly home care volunteer was a multitude of bed ridden elder, participation with local government organizations is not high and there is a lack of participation from the elders.